IMPROVEMENT OF UNDERSTANDING IN ISLAMIC RELIGIOUS EDUCATION THROUGH AUDIOVISUAL MEDIA - Muhammad, Devy Habibi; Khozin, Khozin; Humaidi, M. Nurul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Many educators use the lecture method, which is less suitable for education in this modern era, causing students to tend to get bored, sleepy, and ultimately reluctant to pay attention. The aim of this study is to improve students' understanding by utilizing audiovisual media periodically and to improve the learning system to make it better than before. The method used in this research is Classroom Action Research, which plays an important role in enhancing the quality of learning. The results of this study show that audiovisual media in Islamic Religious Education learning in class X at SMA Islam Sumberasih Probolinggo significantly improved students' learning outcomes. In the pre-cycle stage, the lecture method resulted in a low level of mastery, with few students achieving the required score. After the application of audiovisual media through two cycles, the level of mastery sharply increased, especially in Cycle II. The number of students in the "Very Good" category also increased.